Tipe Organisasi dan Manajemen Publik Pada Lembaga Pemasyarakatan Kelas I Malang - Ignatius Layola; Padmono Wibowo (Yayasan Daarul Huda Kruengmane, 2023)
Overcrowding, lack of space, security issues, inmate rehabilitation, and human resource management are just some of the problems plaguing correctional institutions in Indonesia. Malang Class I Prison has a residential capacity of 1,282, while in June 2021, there were 3,366 inmates, resulting in a lack of fulfillment of prisoners' rights. Therefore, the need for competent public management is essential to meet these challenges head-on. The aim of this research is to identify the type of organization and public management at Class I Malang Penitentiary. This research uses qualitative research methods with a case study of Malang Class I Prison as the subject. The research results reveal that public management in prisons is the key to achieving effectiveness, efficiency and accountability in the correctional system. However, there are many obstacles such as overcrowding, lack of resources, lack of competent staff, security problems, tension between inmates, regulatory uncertainty, and community stigma, which affect organizational management in Malang Class I prisons. Good public management can improve operational efficiency, quality public services, risk and security management, staff development, and accountability and transparency. Therefore, the role of public management in Malang Class I Prison is very important to achieve successful correctional goals and ensure the protection of prisoners' human rights.